CAPACITY BUILDING KADER PKK DALAM MEWUJUDKAN KESEJAHTERAAN KELUARGA DI PADUKUHAN WATUGAJAH GUNUNGKIDUL - Indah Fitriani; Dina Nakita; Putri Intan Permatasari; Mutia Septiyanti; Sayyida Umami; Azroi; Raegil Albert Setiawan; Adib Ubaidillah Mahbub; Muhammad Alfaridzi; , Muhammad Syafi’ul Anam (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2022)
The Family Welfare Empowerment (PKK) of Watugajah sub-village has obstacles in its implementation, including the lack of efficient administrative management, the absence of an effective work program system, and the lack of PKK contributions that have a direct impact on family welfare. This problem is the background of restructuring and capacity bulding program for PKK. This research includes qualitative research and descriptive approach, the object of research to be studied is PKK cadres in Watugajah, Girijati, Purwosari, Gunungkidul. Observation and documentation methods is used for data collectiom. The data analysis technique used in this research is qualitative data analysis. The results of this study are; first, the implementation of mentoring activities, especially related to the preparation of administrative data related to PKK inventory. Second, the direction of PKK cadres in implementing work programs. Third, the increasing contribution of PKK in activities that support family welfare. The findings of this study have significance for the development of PKK performance which has a positive and sustainable impact in Watugajah starting from the formation of the PKK Organization, increasing the quality of human resources, and the impact of contributions in family welfare, especially in maintaining the economy and family health.